Caregivers' voices: From the world of autism spectrum disorder - Patience M.M. Dira; Rorisang J. Machailo; Suegnet Scholtz (AOSIS, 2024)
Background: Caring for a child with autism spectrum disorder (ASD) is a challenging and stressful task, especially in countries with limited resources. Additional research is necessary, considering the increasing prevalence of children with ASD, to gain increased knowledge of the complex difficulties faced by caregivers of ASD children and to offer insights into the coping strategies and support networks that parents utilise. Objectives: The objective of this study was to explore and describe the experiences and coping mechanisms of caregivers of children with ASD in Dr Kenneth Kaunda district, North West province, South Africa. Method: Qualitative explorative, contextual and descriptive design with purposive sampling technique and semi-structured interviews were conducted. Data were analysed following the six steps of reflexive thematic analysis. Results: Two themes were identified: Caregivers' experiences in raising a child with autism, and caregivers' coping in raising a child with autism. Conclusion: The research established caregivers' experiences and coping mechanisms in raising a child with ASD and the effects on different aspects of their lives including emotional, social and financial aspects, which contribute negatively to their holistic well-being. These impediments warrant the establishment of emotional support groups, empowerment of caregivers and awareness-raising through campaigns to educate the family and the community on the diverse challenges. Contribution: The findings of this study contribute to a deeper understanding of the multifaceted challenges faced by caregivers of children with ASD and provide insights into the support systems and coping mechanisms employed by these caregivers within the socio-ecological context.